Astrovirus gastroenteritis in hospitalized children of less than 5 years of age in Taiwan, 2009 - Tseng, Wei-Chen; Wu, Fang-Tzy; Hsiung, Chao A.; Chang, Wan-Chi; Wu, Ho-Sheng; Wu, Ching-Yi; Lin, Jen-Shiou; Yang, Shun-Cheng; Hwang, Kao-Pin; Huang, Yhu-Chering (Journal of microbiology, immunology and infection, 2012)
Acute gastroenteritis is a common illness in children under 5 years old. Although rotavirus is a leading cause, other viruses including astrovirus are also important, but have been the subject of limited studies. This is a prospective study to investigate astrovirus gastroenteritis in hospitalized children in Taiwan. From January 2009 to December 2009, children below 5 years of age admitted to three hospitals in Taiwan due to acute gastroenteritis were eligible for this study. Stool specimens were sent for the detection of astrovirus by reverse transcriptase polymerase chain reaction; once positive for astrovirus, the sequencing and phylogenetic analysis of each strain was performed. A total of 989 children were enrolled during the study period. The overall positive rate of astrovirus was 1.6%, ranging from 1.03% to 2.26% in different hospitals, while rotavirus accounted for 20.2% of the patients. Six of the 16 children (37.5%) with astroviral infection had documented coinfection with rotavirus. The median age of infection was 28.2 months. The seasonal distribution of astrovirus peaked from April to June. Diarrhea alone (40% vs. 2.1%, p < 0.0001) was significantly more commonly seen than the triad of fever, vomiting and diarrhea (30% vs. 71%, p = 0.0062) in children with astroviral infection alone than in those with rotaviral infection alone. The mean duration of diarrhea was significantly longer in patients with mixed infection than those with astroviral infection alone (6.8 vs. 4.2 days, p = 0.013). Respiratory symptoms were noted in 10 children (62.5%). Serotype HAstV-1 was the most common (68.8%). Astrovirus accounted for 1.6% of infections in children under 5 years hospitalized with acute gastroenteritis in Taiwan. Compared with those caused by rotavirus, the incidence of gastroenteritis in hospitalized children caused by astrovirus was low and the disease severity was mild.